Hydrological Characteristics of the Visakhapatnam Harbour - Murthy, K.V.S.; Ramam, K.V.S. (Defence Science Journal, 2014)
Studies on the distribution of temperature and salinity in the Visakhapatnam harbour during the months of November-December 1966 and June-July 1967, showed marked seasonal variations. In winter both the temperature and salinity values are low throughout the depth column, while in late summer there is a significant increase in their values. The effect of tide and rainfall on the hydrological parameters has been discussed.